Nursing Development should Now Become a Priority for Health Systems in Europe - SKELA-SAVIČ Brigita (Sciendo, 2023)
The vast majority of European countries are struggling to embrace nursing as a profession and as a science. There are still not enough nurses with bachelor's degrees and advanced practical skills, and clinical specialisations for nurses are being developed at the master's level. Attention should be paid to recognising nurses as an equal healthcare workforce who need to be empowered to advance their profession and be provided with professional development opportunities. Changes needed include improving pay and working conditions, providing opportunities to improve skills and professional recognition, empowering nurses to deliver care, and harnessing the power of technology to better support nurses. The declining interest in nursing education and the often stereotypical and condescending view of the role and work of nurses on the healthcare team should be a warning signal to all who are working on healthcare reform.